Study of Hematological and Biochemical Parameters in Runners Completing a Standard Marathon - Reid, S. A.; Speedy, D. B.; Thompson, J.; Noakes, T. D.; Mulligan, G.; Page, T.; Campbell, R.; Milne, C. (Clinical Journal of Sport Medicine, 2004)
Objective: To study hematological and biochemical parameters prospectively in runners completing a standard 42.2-km marathon run. To determine the incidence of hyponatremia in runners, and whether consumption of nonsteroidal anti-inflammatory medications (NSAIDs) was associated with alterations in serum biochemical parameters. Design: Observational cohort study. Setting: City of Christchurch (New Zealand) Marathon, June 2002. Participants: One hundred fifty-five of the 296 athletes entered in the 2002 City of Christchurch Marathon were enrolled in the study. Main Outcome Measures: Athletes were weighed at race registration and immediately after the race. Blood was drawn postrace for measurement of serum sodium, potassium, creatinine, and urea concentrations and for hematological analysis (hemoglobin concentration, hematocrit, leukocyte distribution). Results: Complete data sets including prerace and postrace weights, and postrace hematological and biochemical analyses were collected on 134 marathon finishers. Postrace serum sodium concentrations were directly related to changes in body weight (P < 0.0001). There were no cases of biochemical or symptomatic hyponatremia. Thirteen percent of runners had taken an NSAID in the 24 hours prior to the race. Mean values for serum creatinine (P = 0.03) and serum potassium (P = 0.007) concentrations were significantly higher in runners who had taken an NSAID. No athlete who had taken an NSAID had a postrace serum creatinine concentration less than 0.09 mmol/L. Ninety-eight percent of runners had a postrace leukocytosis (mean white cell count, 18.97 b/L), of which the major component was a raised neutrophil count (mean neutrophil count, 15.69 b/L). Conclusions: This study found no cases of hyponatremia in runners completing a standard distance marathon. This finding relates to a marathon run under ideal conditions (minimal climatic stress) and in which there were fewer aid stations (every 5 km) than is common in North American marathons (every 1.6 km). Also, aggressive hydration practices were not promoted. Consumption of NSAIDs in the 24 hours prior to distance running was associated with altered renal function.